A contrastive analysis of english and vietnamese real estate adertising slogans in printed advertisements - Nguyen, Thi Thu Thao (University of Languages and International Studies, 2017)
Due to the high demand of current market, every product needs effective strategies to introduce its image to the potential customers, and a successful slogan seems to be an impressive way. Among various types of products, real estate is gradually paid much attention for its significance in people‟s living condition. However, there exist differences in terms of linguistic features between English and Vietnamese real estate slogans that need to be investigated. Therefore, the study “A Contrastive Anal ysis of English and Vietnamese Real Estate Advertising Slogans in Printed Advertisements” is conducted to figure out some distinctive phonological, lexical and syntactic features among English and Vietnamese real estate slogans. The total of 90 advertising slogans are collected from well-known English and Vietnamese real estate newspapers and magazines, and analyzed to support the aim of the study. The finding of the research emphasizes the similarities and differences in terms of phonological, lexical and syntactic features between English and Vietnamese real estate advertising slogans. The thesis was carried with the hope to implement some suggestions for teaching and learning business English, and some advice for advertisers.